SEEING DEMONS: AUTOPSY IN MAXIMUS OF TYRE'S ORATION 9 AND ITS ABSENCE IN APULEIUS' ON THE GOD OF SOCRATES. (6th May 2016) - Benson, Geoffrey C.
Abstract : Apuleius' On the God of Socrates ( De Deo Socratis ), a lecture on Platonic demonology and Socrates' daimonion that dates to the second half of the second century CE, is a critical work in the assessment of Apuleius' Platonism, but it also should play a larger role in our reconstruction of his public image than it has. This popular philosophical lecture focuses on the same theme as two Greek works from roughly the same time period: Plutarch's dialogue On the Daimonion of Socrates (περὶ τοῦ Σωϰράτους δαιμονίου) and Maximus of Tyre's Orations 8-9 (Διαλέξεις). Discussion of On the God of Socrates has centered on its relationship with these other texts, with the aim of comparing Apuleius' argument about daimones with Plutarch's and Maximus'. The consensus view is that Plutarch's treatment of demonology has little in common with Apuleius' (I present further evidence supporting the consensus near the end of this essay). On the other hand, many scholars assert Apuleius' closest Greek model is Maximus of Tyre, a sophist with a Platonic orientation who wrote forty-one brief lectures on ethics and other philosophical subjects in the second century CE.